A CT-guided robotic needle puncture method for lung tumours with respiratory motion. (May 2020) - Wei, Lin; Jiang, Shan; Yang, Zhiyong; Zhang, Guobin; Ma, Liang
Highlights: A method is proposed to handle the respiratory motion of tumours for lung puncture. Dynamic visualization provides rendered image synchronized with actual breathing. Robotic insertion strategy allows the needle to be inserted under free breathing. The respiratory signal is converted into an analytical signal by Hilbert transform. The method achieves high insertion accuracy in the face of moving targets. Abstract: Purpose: Percutaneous interventions rely on needle puncture to deliver medical devices into lesions. For lung tumours, respiratory motion makes effective puncture procedures difficult to achieve. To address this issue, a needle puncture method considering respiration is proposed to improve the accuracy of lung puncture. Methods: The accuracy of puncture is ensured by visualization and needle guidance. Dynamic visualization of the respiratory motion is developed for needle path planning based on four-dimensional computed tomography (4DCT) images. The rendered image is synchronized with the actual breathing by using respiratory signals. A robotic needle insertion strategy for velocity adjustment based on these respiratory signals is designed to guide the needle towards the moving tumour. Results: The dynamic visualization was tested on multiple 4DCT datasets and achieved a frame rate of over 32 frames per second (FPS). A computer simulation was carried out to verify the feasibility of the needle insertion strategy. Needle puncture was performed on a phantom, and a mean accuracy of 1.34 ± 0.18  mm was achieved. Conclusions: In this paper, an efficient and robust method is proposed to improve the visualization and targeting of lung puncture, which reduces the impact of respiratory motion on the accuracy.